PENERAPAN PRINSIP JUAL BELI DENGAN SISTEM PAYLATER DALAM PERSPEKTIF HUKUM ISLAM - Ariko, Muhammad; Kartoningrat, Raden Besse (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2024)
Current technological advances allow humans to be able to transact using information technology, this is no exception in terms of buying and selling. In the buying and selling system, the payment has also developed, namely the Paylater system. While the existence of this payment system is the category of usury in the perspective of Islamic law. So this research was conducted to examine this matter, how the application of the principle of buying and selling using the Paylater system in the perspective of Islamic Law. So that from the study that the author found, namely in buying and selling according to Islamic law there is the principle of tawhid, the principle of justice, the principle of honesty, the principle of willingness/freedom, and the principle of maslahat or benefit. The research method in this study is normative with a conceptual and statutory approach. So that from these existing principles, the author relates the indicators and implementation of these principles to the Paylater system which from the study can be concluded that the various Paylater payment systems carried out by online buying and selling applications in Indonesia have their own characteristics or characteristics which in the end the use of the Paylater system is not in accordance with Islamic law because there is an element of usury in it because of the debt (Al-Qardh) that exists in the system.